Staging the World : Chinese Nationalism at the Turn of the Twentieth Century - Karl, Rebecca E. (Book collections on Project MUSE., 2002)
An historical analysis of how the Chinese constructed their understandings of their place in the world in the late nineteenth and early twentieth centuries.